Suppressed superconductivity in substrate-supported β12 borophene by tensile strain and electron doping. (17th February 2017) - Cheng, Cai; Sun, Jia-Tao; Liu, Hang; Fu, Hui-Xia; Zhang, Jin; Chen, Xiang-Rong; Meng, Sheng
Abstract: Planar borophene, the truly 2D monolayer boron, has been independently successfully grown on Ag(1 1 1) by two groups (2016 Nat. Chem .8 563 and 2015 Science 350 1513), which has received widespreading attentions. The superconducting property has not been unambiguously observed, which is unexpected because light element boron should have strong electron–phonon coupling. To resolve this puzzle, we show that the superconducting transition temperature T c of β 12 borophene is effectively suppressed by the substrate-induced tensile strain and electron doping via first principles calculations. The biaxial tensile strain of 2% induced by Ag(1 1 1) significantly reduces T c from 14 K to 2.95 K; electron doping of 0.1 e − per boron atom further shrinks T c to 0.09 K. We also predict that the superconducting transition temperature in β 12 can be enhanced to 22.82 K with proper compressive strain (−1%) and 18.97 K with hole doping (0.1 h + per boron). Further studies indicate that the variation of T c is closely related to the density of states of σ bands near the Fermi surface. Our results help to explain the challenges to experimentally probe superconductivity in substrate-supported borophene.